Patenabilitas Algoritma Artificial Intelligence dalam Hukum Paten Indonesia: Rekonstruksi Parameter Perlindungan Hukum - Sitta Khairunnisa; Intan Sukmawati; Ikhwan Aulia Fatahillah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed technological innovation, making AI algorithms central to developments across healthcare, finance, manufacturing, and autonomous systems. Despite their growing economic and technological significance, the patentability of AI algorithms remains legally uncertain in Indonesia. Existing studies have predominantly examined software patent protection or AI-related intellectual property from a general perspective, while limited attention has been given to establishing normative parameters for determining the patentability of AI algorithms under the Indonesian Patent Law. This research addresses that gap by analyzing the juridical challenges arising from Article 4 letter (d) of Law Number 13 of 2016 concerning Patents and formulating an adaptive legal framework for AI algorithm patentability. This study employs normative juridical research using statutory, conceptual, and comparative approaches by examining Indonesian patent regulations alongside the practices of the European Patent Office (EPO) and the United States Patent and Trademark Office (USPTO). The findings reveal that the categorical exclusion of computer programs has created a protection vacuum, as copyright protection safeguards only the expression of source code rather than the technical functions and computational logic embodied in AI algorithms. Comparative analysis demonstrates that both the EPO and USPTO have adopted functional approaches through the doctrines of technical character, technical effect, and inventive concept, enabling AI-related inventions that produce concrete technical solutions to qualify for patent protection. This study contributes by proposing a normative reconstruction of Indonesia's patent system through the adoption of substantive examination parameters based on technical contribution, technical integration, and inventive step, thereby providing a conceptual framework for future patent examination guidelines. The proposed model is expected to strengthen legal certainty, promote technological innovation, and support the development of a more adaptive national patent system in response to the digital economy